Enkele opmerkinge oor die studiegebied van die Kommunikasiekunde - D.F.M. Strauss (Communicare)
A few remarks concerning the field of study of communication science. To account for the nature of any special science is not itself a special scientific concern, as it needs a basic philisophical perspective. It is not sufficient to define the uniqueness of the scientific endeavour in terms of features like systematics, verification/falsification, method, and the so-called relation between a knowing subject and a study-object. Any concrete entity (object') functions at different modes of being (modal- ities), such as the numerical mode (aspect), the spatial modality, the sensitive sphere (sometimes passively as a sensed object), the logical aspect (for instance as something analizable, i.e. identifiable and distinguishable), the sign-aspect (for example its name), the social aspect, etc. The fundamental question therefore is not, what object is scientifically studied, but from what angle (aspect, mode) is this or that entity approached? These different modalities do indeed serve as special scientific approaches (points of entry) to reflect on concrete reality. In order to think scientifically, one has to focus one's attention on a specific modal perspective, disregarding other modal directions of approach. Because abstraction as such occurs frequently in our non-scientific daily life, it is not sufficient to qualify scientific activities. In fact, abstraction and analysis imply each other. To analyse anything implies an act of identification and and abstraction concerns the identification of something for some characteristic) by disregaring (ie. distinguishing it from) non-relevant things for features) Scientific acuvities display a specific kind of analysis, namely modal analysis (abstraction) However, the identification of a modality delimiting the field of study of a special science always implies that one must simultaneously distinguish it from other modalities. This stresses the necessity of e philosophical view on the coherent diversity of modal aspects The uniqueness of these modal aspects explains the inherent limits of conceptual definition in the final analysis, every definition depends on primitive indefinable terms. This insight is lofts applied to the notion of communication and explored in the direction of the disclosed suure of the sign-mode An account is given of the implied object-object object subject relation of communication in the socially disclosed sign-aspect. To explain the nature of various types of communication an appeal is made to different kinds of social intercourse, classified as consociational, communal and associational relationships. The conditions of meaning (presupposing choice) and interpretation point to the typical human character of communication as it is conceived of in this analysis.